2022
DOI: 10.3390/jintelligence11010002
|View full text |Cite
|
Sign up to set email alerts
|

Abstract Graphic Creativity, Feelings about School, and Engagement in the School Environment: What Are the Interindividual Differences between Gifted and Non-Gifted Children?

Abstract: This study examines interindividual differences between gifted and non-gifted children in the school environment. Three distinct measurement tools were used to enable a multimodal approach of gifted and non-gifted children with abstract graphic creativity, feelings about school and engagement in the school environment being considered. The results obtained from 328 children (including 45 gifted children) revealed that the gifted children obtained scores significantly higher than non-gifted children in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 94 publications
0
0
0
Order By: Relevance
“…Finally, there is a trend evolution between the AAS score and the child level: the child's commitment increases slowly each year from first grade to third and fourth grade, before falling back in fifth grade. This trend has been confirmed in another study we conducted with this scale, for the sub-dimension F2-PT (i.e., associated with the teacher-student relationship) [3].…”
Section: External Validitysupporting
confidence: 76%
See 3 more Smart Citations
“…Finally, there is a trend evolution between the AAS score and the child level: the child's commitment increases slowly each year from first grade to third and fourth grade, before falling back in fifth grade. This trend has been confirmed in another study we conducted with this scale, for the sub-dimension F2-PT (i.e., associated with the teacher-student relationship) [3].…”
Section: External Validitysupporting
confidence: 76%
“…The relevance of asking children directly about their experiences of commitment in school to examine whether teacher observation is correlated with children's perceptions of their commitment in school has been already investigated in a recent study. In this study, using the French FAS [30] and the AAS, an interesting gap between gifted students and teacher perception of their relationship has been revealed that has not been observed for non-gifted students [3]. Incidentally, this result confirms the interest of the existence of this scale to study inter-individual differences in commitment at school, in the field of differential psychology.…”
Section: Limitations and Research Perspectivessupporting
confidence: 70%
See 2 more Smart Citations
“…There are several reasons to suspect that the gap between creativity at school and creativity at home would be smaller for the gifted sample. First, evidence suggests that gifted students typically display more creative thinking than their nongifted peers (Abdulla Alabbasi et al, 2021a;American Psychological Association, 2017;Davis et al, 2011;Renzulli, 2005;Sanchez & Blanc, 2023a). This may provide them with robust creative tendencies that are more stable across contexts.…”
Section: Is Creativity Expressed At Home Related To Creativity Expres...mentioning
confidence: 99%